THE ROLE OF LIBRARIANS IN HEALTH INFORMATION DIFFUSION IN THE DIGITAL AGE - Olubanke M Bankole; Isaac O Busayo (International Studies Journal)
Access to reliable health information source builds knowledge that individuals need to take informed decisions that will promote their health and well-being. Inadequate/lack of access to reputable information creates a gap in knowledge of health problems, ultimately leading to poor health decisions and outcomes. In Nigeria, there are several sources such as health workers, mass media, textbooks and internet through which health information are disseminated to the public and patients, but libraries and librarians are often not considered as part of the explicit plan to advance the health of the populace. The paper therefore provides an overview of the role that libraries could play to promote diffusion of information for quality health care in Nigeria drawing from examples of such practices in developed countries. Librarians as repositories of knowledge could be involved in helping the public to get high quality consumer health information, in providing patients’ education and in imparting information literacy skills which avails individuals the understanding of their health status, and take appropriate actions to prevent and control diseases. Information prescription entails the librarians providing personalized or customized information to patients on the request of the consulting physicians thereby improving patients’ ability to manage and control his/her medical condition. The library could further engage in outreach to take health information to grassroots and are also relevant in emergency response and preparedness.